Investigating relationships between ancestry, lifestyle behaviors and perceptions of heart disease and breast cancer among Canadian women with British and with South Asian ancestry. (April 2018) - Curtin, Kimberley D; Berry, Tanya R; Courneya, Kerry S; McGannon, Kerry R; Norris, Colleen M; Rodgers, Wendy M; Spence, John C
Background: Ethnic minority groups including Asians in Canada have different knowledge and perceptions of heart disease and breast cancer compared with the ethnic majority group. Aim: Examine relationships between perceptions of heart disease and breast cancer, and lifestyle behaviors for Canadian women with British and with South Asian ancestry. Methods: Women with South Asian ( n = 170) and with British ( n = 373) ancestry ( M age = 33.01, SD = 12.86) reported leisure time physical activity, intended fruit and vegetable consumption, disease perceptions (ability to reduce risk, control over getting the diseases, and influence of family history), and demographic information. Mann–Whitney tests and multiple hierarchical linear regressions were used to examine the relationships between lifestyle behaviors and disease perceptions, with ancestry explored as a possible moderator. Results: Participants with South Asian ancestry believed they had greater ability to reduce their risk and have control over getting breast cancer than participants with British ancestry. Family history influences on getting either disease was perceived as higher for women with British ancestry. Age was positively related to all three perceptions in both diseases. Intended fruit and vegetable consumption was positively related to perceptions of ability to reduce risk and control of both diseases, but was stronger for women with South Asian ancestry regarding perceptions of breast cancer. Leisure time physical activity was positively related to perceptions of control over getting heart disease for women with British ancestry. Conclusions: Women's disease perceptions can vary by ancestry and lifestyle behaviors. Accurate representation of diseases is essential in promoting effective preventative behaviors.